Knowledge, attitude and practice on diet and physical activity among mothers with young children in the Jhaukhel-Duwakot Health Demographic Surveillance Site, Nepal - Natalia Oli; Abhinav Vaidya; Katja Pahkala; Gabriele Eiben; Alexandra Krettek (PUBLIC LIBRARY SCIENCE, 2022)
The prevalence of cardiovascular diseases is increasing in low and middle-income countries; Nepal's population shows a high prevalence of behavioral risk factors. Our cross-sectional study in the Jhaukhel-Duwakot Health Demographic Surveillance Site (JD-HDSS), located near the capital Kathmandu, explored knowledge, attitude, and practice (KAP) of mothers with young children regarding diet and physical activity and mothers' perception of their children's attitude and behavior toward the same issues. The purpose of our study was to assess needs of the mothers concerning cardiovascular health in general and more specifically regarding diet and physical activity, and to establish a baseline for future intervention in the community by comparing two villages of JD-HDSS. In August-November 2014, nine trained enumerators interviewed all mothers of children aged 1-7 years (N = 962). We scored responses on dietary and physical activity KAP, then categorized the scores based on the percentage obtained out of the maximum possible scores into "poor," "fair," and "good." More highly educated mothers scored higher for KAP (all p<0.001); the children's behavior score reflected their mother's education level (p = 0.007). Most respondents were unfamiliar with the concept of healthy and unhealthy food. Overall, 57% of respondents in JD-HDSS had "good" knowledge, 44.6% had "good" attitude, and most (90%) had "poor" practice. We observed no significant differences between the villages regarding mothers' knowledge and attitude or children's behavior. Practice score of mothers in Jhaukhel was higher than those in Duwakot regarding diet and physical activity (p<0.001). Mothers' perceived barriers for improving lifestyle were high cost of healthy food, taste preference of other family members, and lack of knowledge regarding healthy food. Barriers for physical activity were lack of leisure time, absence of parks and playgrounds, busy caring for children and old people, feeling lazy, and embarrassed to be physically active in front of others. Our findings suggest that a health education intervention promoting a healthy lifestyle for mothers and children might improve KAP and also improve cardiovascular health. To address mothers' gap between knowledge and practice, a future intervention should consider perceived barriers.